Assessing the Growth and Performance of Crop Insurance Schemes in India: Trends, Challenges and Opportunities - Sharon, Mandepudi Mary; Pavani, Mangalapuri; Aparna, B. (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
This study assessed the growth and performance of key crop insurance schemes, including yield-based crop insurance schemes such as the National Agricultural Insurance Scheme (NAIS) and the Pradhan Mantri Fasal Bima Yojana (PMFBY), as well as weather-based crop insurance schemes like the Weather-Based Crop Insurance Scheme (WBCIS) and the Restructured Weather-Based Crop Insurance Scheme (RWBCIS). Secondary data was collected for the period from 1999-2000 to 2023-24, covering statistical indicators such as the number of farmers insured, total area covered, total premium collected, and total claims paid under NAIS, PMFBY, WBCIS, and RWBCIS. The analysis of yield-based crop insurance schemes revealed significant growth in farmer participation, insured area, premium collection, and claims disbursement. In contrast, weather-based crop insurance schemes exhibited fluctuating trends in participation and financial performance. Indicators such as insured area and total insured value showed positive growth but a decline in farmer participation remained a concern.